Geographical Information System Mapping Based on Android at Equal Senior High School In Lubuklinggau - Joni Karman; Ema Crisdiyanti (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2019)
The problem in this study is there is no geographic information system for mapping senior high schools so that there is a misunderstanding inlocation delivery at aqual Senior high schools (SMA) in Lubuklinggau. This research uses data collection methods, by making observations at the research site, conducting question and answer directly to the source, and documentation by reading literature books. The results of the study show that the program on the geographic information system mapping on Android based equivalents on Android at Lubuklinggau the geographical information system is expected to be a solution for the community in finding the location of Senior High Schools in Lubuklinggau. This application was created using the C I framework and also the ionic framework supported by api Google Maps.